Fourier-Legendre Pseudospectral Method for the Navier-Stokes Equations (Journal of Computational Mathematics, 2000)
In this paper, we construct a Fourier-Legendre pseudospectral scheme for the unsteady Navier-Stokes equations. This method easily deals with nonlinear terms and saves computational time. The strict error estimations are given.
Keywords: Navier-Stokes equations; Fourier-Legendre pseudospectral method; error estimation.